Potensi Limbah Cair Pabrik Kelapa Sawit sebagai Bahan Bakar Kompor Portabel Berbasis Internet Of Things - Ali Usman; Ari Wibowo; Muhammad Ridho Ramadhan; Rahmad Hari Purnomo (xxxx-xxxx, 2020)
Usman A, Wibowo A, Ramadhan MR, Purnomo RH. 2020. Palm oil mill effluent potency as a fuel for portable stove with internet of things-based monitori. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Palm oil mill effluent processing in general is still carried out conventionally. However, this process requires a large area. In addition, conventional waste ponds can produce methane (CH4) and carbon dioxide (CO2) which cause the greenhouse effect. If not treated properly, the palm oil mill effluent can give bad impacts to the environment. This paper contains the potential of palm oil liquid waste into biogas energy which is applied to portable stoves with Internet of Things (IoT)-based monitoring. The potential of palm oil mill effluent is studied based on in-depth and extensive literatures. The processing of palm oil mill effluent into biogas energy can be done with anaerobic digester technology which is added with one or two different substrates. To increase the percentage of methane gas, pressure swing absorption technology can be used. The sensor used for monitoring is adjusted to the observed parameters. The MQ2 sensor is used as gas leak detector, a load cell and the HX711 module are used  as a load detector for gas cylinder, and LM35 is used as a temperature detector. Palm oil mill liquid waste has a potential to become biogas energy which can be applied in portable stoves with a Internet of Things (IoT)-based monitoring.